2013
DOI: 10.1186/1755-8166-6-37
|View full text |Cite
|
Sign up to set email alerts
|

Banding cytogenetic analysis in pediatric patients with acute lymphoblastic leukemia (ALL) in a Brazilian population

Abstract: BackgroundCytogenetic studies in Brazilian population about childhood acute lymphoblastic leukemia (ALL), the most common childhood malignancy, are scarce. Moreover, Brazilian race is very heterogeneous and is made by the confluence of people of several different origins, from the original Native Brazilians, with the influx of Portuguese colonizers, Black African slaves, and recent European, Arab and Japanese immigration. The purpose of this prospective, multicentric study was to assess the sociodemographic, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Approximately 75% of childhood ALL cases harbor CAs detected by conventional cytogenetics and FISH. However, the percentage varies from 55 up to 89% in different series 200 depending on the number of patients studied, the year they were reported, and the populations where they have been studied [Chessels et al, 1997;Andreasson et al, 2000;Forestier et al, 2000;De Braekeleer et al, 2010;Moorman et al, 2010;Gil et al, 2013]. We report the cytogenetic findings in 1,057 children with ALL studied in our center, spanning a period of 23 years.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 75% of childhood ALL cases harbor CAs detected by conventional cytogenetics and FISH. However, the percentage varies from 55 up to 89% in different series 200 depending on the number of patients studied, the year they were reported, and the populations where they have been studied [Chessels et al, 1997;Andreasson et al, 2000;Forestier et al, 2000;De Braekeleer et al, 2010;Moorman et al, 2010;Gil et al, 2013]. We report the cytogenetic findings in 1,057 children with ALL studied in our center, spanning a period of 23 years.…”
Section: Discussionmentioning
confidence: 99%
“…Cytogenetic analysis in hematological malignancies like many other diseases, plays a significant role in understanding the pathophysiology as well as clinical behavior of the condition (Mazloumi et al, 2012;Gil et al, 2013). In fact, for acute lymphoblastic leukemia, like other malignant conditions, karyotype is one of the prognostic indicators (Borowitz et al, 2008;Iacobucci et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Another previous study 13 showed chromosomal abnormalities in 64% of cases. The numerical abnormalities involved 53% of the cases followed by 26% cases revealing structural abnormalities.…”
Section: Resultsmentioning
confidence: 77%